Evolving phenotype of Marfan's syndrome. Issue 1 (1st January 1997) - Lipscomb, Karen J; Clayton-Smith, Jill; Harris, Rodney
Abstract : AIM: To examine evolution of the physical characteristics of Marfan's syndrome throughout childhood. METHODS: 40 children were ascertained during the development of a regional register for Marfan's syndrome. Evolution of the clinical characteristics was determined by repeat evaluation of 10 patients with sporadic Marfan's syndrome and 30 with a family history of the condition. DNA marker studies were used to facilitate diagnosis in those with the familial condition. RESULTS: Musculoskeletal features predominated and evolved throughout childhood. Gene tracking enabled early diagnosis in children with familial Marfan's syndrome. CONCLUSIONS: These observations may aid the clinical diagnosis of Marfan's syndrome in childhood, especially in those with the sporadic condition. Gene tracking has a role in the early diagnosis of familial Marfan's syndrome, allowing appropriate follow up and preventive care.